Моделювання комбінованого діода Шоттки - Кісельов, Є.М. (Проблемы машиностроения, 2013)
Средствами системы TCAD Studio рассмотрены статические и динамические характеристики двухмерной конечно – разностной модели комбинированного диода Шоттки. Показано, что эффективность управления диодом зависит от величины напряжения на дополнительном электроде –затворе. Установлено, что степень регулирования дополнительной емкости, согласно модели, имеет значение примерно 22% . Засобами системи TCAD Studio розглянуто статичні і динамічні характеристики двовимірної скінченноелементної моделі комбінованого діода Шоттки. Показано, що ефективність керування діодом залежить від величини напруги на додатковому електроді – затворі. Встановлено, що ступінь регулювання додаткової ємності, згідно з моделюі, має значення близько 22 %. Despite the fact that various designs of Schottky diodes with additional gate were developed and investigated, still little attention has been paid to the simulation of their operation modes at independent change of field electrode potential. The results of two-dimensional physical-topological simulation of combined Schottky diode with electrically separated anode and gate in the computer-aided design system TCAD Studio are given in the paper. Analysis of the obtained results shows that the management effectiveness of combined Schottky diode depends on the voltage value on the additional electrode-gate. The regulation degree of additional diode capacitance, according to the applied model has a value of about 22%. The research results can be used for further optimization of designs of combined Schottky diodes.